Acoustic simulation of underwater communication network with fixed and transponder nodes in a sea platform and performance study using MCDMA - Vijayalakshmi, P; Rajendran, V (International Journal of Engineering and Technology, 2018)
The field of underwater acoustic communication has been developing innovatively to help the growth of mankind in various fields and in many underwater applications. Modulation techniques like FDMA and TDMA in underwater acoustic is very difficult because it uses elec-tromagnetic waves, which will be attenuated due to conductivity. So here, we use the acoustic waves to transmit the data between the nodes by using CDMA algorithm because of its high spectral efficiency and limited bandwidth usage. VBF (vector based forward) routing proto-col is used for data transmission between the fixed nodes and anchoring node. The comparative study reveals that the performance of delay constrained CDMA shows better throughput and PDR when compare with existing CDMA.Â